2020
DOI: 10.1371/journal.pone.0237666
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion to oviduct glycans regulates porcine sperm Ca2+ influx and viability

Abstract: Before fertilization, sperm bind to epithelial cells of the oviduct isthmus to form a reservoir that regulates sperm viability and capacitation. The sperm reservoir maintains optimum fertility in species, like swine, in which semen deposition and ovulation may not be well synchronized. We demonstrated previously that porcine sperm bind to two oviductal glycan motifs, a biantennary 6-sialylated N-acetyllactosamine (bi-SiaLN) oligosaccharide and 3-Osulfated Lewis X trisaccharide (suLe X). Here, we assessed the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 61 publications
4
22
0
Order By: Relevance
“…But there was no effect on motility detected using CASA analysis, consistent with our prior findings [19]. We assessed capacitation by the frequency of induced acrosome reactions using conditions in which sperm that have not completed capacitation do not acrosome react [19]. Although there is evidence that oxidative phosphorylation increases during sperm capacitation [39], we did not detect any change in the frequency of ionophore-stimulated acrosome reactions in sperm incubated with suLe X after 4 hr.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…But there was no effect on motility detected using CASA analysis, consistent with our prior findings [19]. We assessed capacitation by the frequency of induced acrosome reactions using conditions in which sperm that have not completed capacitation do not acrosome react [19]. Although there is evidence that oxidative phosphorylation increases during sperm capacitation [39], we did not detect any change in the frequency of ionophore-stimulated acrosome reactions in sperm incubated with suLe X after 4 hr.…”
Section: Discussionsupporting
confidence: 86%
“…If sperm had lowered ETC activity due to reduced ubiquinone, the reduction in oxidative phosphorylation could affect sperm motility and capacitation. But there was no effect on motility detected using CASA analysis, consistent with our prior findings [19]. We assessed capacitation by the frequency of induced acrosome reactions using conditions in which sperm that have not completed capacitation do not acrosome react [19].…”
Section: Discussionsupporting
confidence: 83%
“…Fucosylated glycans of the apical surface of the bovine isthmus oviduct are involved in a specific interaction between bovine sperm and oviduct epithelium [ 52 ] and in retaining sperm for reservoir formation and for extending sperm lifespan [ 27 ]. Moreover, porcine sperm bind to specific sialylated N-linked glycans to form the oviduct reservoir [ 53 ] and to regulate sperm Ca 2+ influx, capacitation, and sperm lifespan [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…For each replicate, semen was sourced from Prairie State Semen Supply, Champaign, IL or PIC, Hendersonville, TN, collected from at least 3 mature boars by ejaculation induced by manual pressure on the glans penis. Semen was extended in Preserve XLT extender (Continental Plastics, WI) to 3 billion cells per 80 ml dose, cooled to 17 °C, transported to the laboratory, and processed within 24 h, as described before 8 , 9 , 13 .The extended semen was pooled and 3 mL were washed through a Percoll cushion containing a mixture of 4 mL of dmTALP (2.1 mM CaCl 2 , 3.1 mM KCl, 1.5 mM MgCl 2 , 100 mM NaCl, 0.29 mM KH 2 PO 4 , 0.36% lactic acid, 26 mM NaHCO 3 , 0.6% BSA, 1 mM pyruvic acid, 20 mM HEPES pH 7.3, sterile filtered), 0.6 mL of 10X HBS (1.3 M NaCl, 40 mM KCL, 10 mM CaCl 2 , 5 mM MgCl 2 , 140 mM fructose, 5% BSA, sterile filtered), and 5.4 mL of Percoll for 10 min at 800 × g. The supernatant was discarded, and the resulting pellet was re-suspended in 14 mL of dmTALP and centrifuged for 3 min at 600 × g. Once again, the supernatant was discarded, and the resulting pellet was re-suspended in 1 mL of dmTALP. Sperm concentration was estimated by hemocytometer and only samples with greater than 75–80% motile sperm were used for experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies using porcine cells have demonstrated that sperm bind specifically to glycans containing either of two specific motifs, 3-O-sulfated Lewis X trisaccharide (suLe X ) or a branched oligosaccharide with 6-sialylated lactosamine termini (bi-SiaLN), which are abundant on the isthmic epithelium 4 7 . Binding to these glycans suppresses the normal increase in intracellular Ca 2+ in sperm and extends the lifespan of sperm in vitro 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%